2006
DOI: 10.1021/jp0566764
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Analysis of Structural, Energetic, Electronic, and Defect Properties of Li2O

Abstract: The structural, energetic, and electronic properties of stoichiometric and defective Li(2)O were studied theoretically. The reliability of the Perdew-Wang method in the framework of density functional theory (DFT), and of two DFT/Hartree-Fock hybrid methods (PW1PW and B3LYP), was examined by comparison of calculated and available experimental data. Atom-centered orbitals and plane waves were used as basis functions for the crystalline orbitals. For both cases, the basis set dependence of calculated properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
83
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(119 citation statements)
references
References 57 publications
28
83
3
1
Order By: Relevance
“…In the present work, the diffusion barrier evaluated by DFT calculation was 0.24 eV in the same unit cell (Li 64 O 32 ) with Ref. [12]. Although the DFT calculation results in different techniques range from 0.24 to 0.33 eV, the values obtained in the four models could be significantly small.…”
Section: Properties In the Staticsmentioning
confidence: 58%
See 1 more Smart Citation
“…In the present work, the diffusion barrier evaluated by DFT calculation was 0.24 eV in the same unit cell (Li 64 O 32 ) with Ref. [12]. Although the DFT calculation results in different techniques range from 0.24 to 0.33 eV, the values obtained in the four models could be significantly small.…”
Section: Properties In the Staticsmentioning
confidence: 58%
“…As reference data, the experimental values [5][6][7][8][9][10][11] and the DFT calculation results in Table 1 Summary of the crystalline properties simulated in the four potential models Ref. [12] and the present study are listed, together with the reported results given by the AIM model [13]. The AIM model is one of the most reliable potential models.…”
Section: Model Assessmentmentioning
confidence: 99%
“…Since the quality of the wavefunction and therefore of the energies critically depends on the basis sets (BS), we employed three BS of increasing quality. A denotes the combination of (864-11G31d (Ti) [27], 7-11G1d (Li) [28], and 86-311G1d (S) [27]; in B, the sulfur BS was replaced by cc-pVTZ [29]; in C, sulfur and lithium BS are cc-pVTZ [30], and the titanium BS is a truncated def2-QZVPPD [31] without diffuse functions. In particular, the latter BS can be considered as close to the basis set limit.…”
Section: Methodsmentioning
confidence: 99%
“…[47,48] PW1PW has been applied to calculations of bulk properties of MgO, NiO, CoO, [46] Li 2 B 4 O 7 , [49] B 2 O 3 , [50] and LiO 2 , [51] defect and electronic properties of TiO 2 , [33] LiBO 2 , [52] Li 2 B 4 O 7 , [53] and Li 2 O:B 2 O 3 nanocomposites, [54] electronic properties of Li 2 O-B 2 O 3 compounds, [55] and surface analysis of Li 2 O [56] and B 2 O 3 . [57] In these studies, good agreement between calculated and experimental properties was observed.…”
Section: Methodsmentioning
confidence: 99%